Byron N. Scott papers - Scott, Byron N. (Byron Nicholson), 1903-1991.
Correspondence, memoranda, court brief, newspaper clippings, and magazine articles relating to Scott's defense of William H. Taylor, specialist at the International Monetary Fund and U.S. Treasury Dept., who was accused of espionage by former Soviet spy turned defector, Elizabeth Bentley, in a case heard primarily before the International Organizations Employee Loyalty Board.
U.S. representative from California and lawyer in Washington, D.C.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bentley, Elizabeth; Taylor, William H. -- 1906-; International Monetary Fund -- Employees and officials; International Organizations Employee Loyalty Board; United States. -- Department of the Treasury -- Employees and officials; Defectors; Espionage, Soviet; Spies; Trials (Espionage) -- United States; Lawyers; Representatives, U.S. Congress -- California